1996
DOI: 10.1212/wnl.47.3.678
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous immunoglobulin on muscle weakness and calcium-channel autoantibodies in the Lambert-Eaton myasthenic syndrome

Abstract: Intravenous immunoglobulin improves many antibody-mediated autoimmune disorders, but its mode of action is unknown. We investigated its effects on muscle strength and on the serum titer of the calcium-channel autoantibodies that are likely to be pathogenic in the Lambert-Eaton myasthenic syndrome (LEMS). In a randomized, double-blind, placebo-controlled crossover trial, serial indices of limb, respiratory, and bulbar muscle strength and the serum titer of calcium-channel antibodies in nine patients were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
0
11

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(126 citation statements)
references
References 13 publications
3
112
0
11
Order By: Relevance
“…One Class II placebocontrolled crossover study evaluated IVIg efficacy in 10 patients with Lambert-Eaton myasthenic syndrome (LEMS). 31 As compared with placebo, IVIg showed a modest benefit on vital capacity, limb strength, drinking time, and antibody titer. There are no controlled studies evaluating the effects of IVIg on polymyositis, diabetic polyradiculoplexoneuropathy, or Miller Fisher syndrome.…”
Section: Discussionmentioning
confidence: 98%
“…One Class II placebocontrolled crossover study evaluated IVIg efficacy in 10 patients with Lambert-Eaton myasthenic syndrome (LEMS). 31 As compared with placebo, IVIg showed a modest benefit on vital capacity, limb strength, drinking time, and antibody titer. There are no controlled studies evaluating the effects of IVIg on polymyositis, diabetic polyradiculoplexoneuropathy, or Miller Fisher syndrome.…”
Section: Discussionmentioning
confidence: 98%
“…Others require drugs such as guanidine and 3,4-diaminopyridine that increase the pre-synaptic calcium influx and the acetylcholine release 5,33 . Patients unresponsive to these treatments may respond to corticoids, azathioprine, plasmapheresis and, most recently, endovenous gammaglobulin therapy [34][35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…The simulation showed that for the lower pair, mean endogenous IgG concentration decreased from 12.1 mg/ml at the start of the simulation to a minimum value of 5.3 mg/ml before returning to baseline values; while with the higher pair of values less competition between endogenous IgG and mAb for FcRn binding was seen such that mean endogenous IgG concentration decreased from 12.1 mg/ ml at the start of the simulation to a minimum value of 11 mg/ml before returning to baseline values (data not shown). Data in subjects with calcium-channel autoantibodies showed a 35% decrease in levels of the autoantibodies 4 weeks after a total dose of 2 g/kg of IVIG (34).…”
Section: Target-mediated Drug Dispositionmentioning
confidence: 99%